2020
DOI: 10.1186/s12941-020-00377-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an antibiotic stewardship program on tigecycline use in a Tertiary Care Hospital, an intervention study

Abstract: Background: A drug-oriented antibiotic stewardship intervention targeting tigecycline utilization was launched at Makassed General Hospital, Beirut, Lebanon, in 2016 as a part of a comprehensive Antibiotic Stewardship Program (ASP). In this study, we evaluated the effect of this intervention on changing tigecycline prescription behavior in different types of infections, patient outcome and mortality, along with tigecycline drug use density, when compared to an earlier period before the initiation of ASP. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…TG is a newly introduced broad-spectrum antibiotic among the family glycylcycline descended from family tetracyclines. It approved its efficacy against tetracycline-resistant bacteria aside from its anticancer activity [2,4,5]. On the other hand, several studies have shown a variety of drawbacks associated with the TG regimen including renal insufficiency [18], pancreatitis [17], and hypofibrinogenemia [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG is a newly introduced broad-spectrum antibiotic among the family glycylcycline descended from family tetracyclines. It approved its efficacy against tetracycline-resistant bacteria aside from its anticancer activity [2,4,5]. On the other hand, several studies have shown a variety of drawbacks associated with the TG regimen including renal insufficiency [18], pancreatitis [17], and hypofibrinogenemia [8].…”
Section: Discussionmentioning
confidence: 99%
“…This allows for an expanded spectrum of activity and decreased susceptibility to the development of resistance. Alterations to the tetracycline structure allow for TG to maintain activity against tetracycline-resistant organisms including resistant Gram-positive organisms [4][5][6]. Based on this therapeutic importance, TG has gained more attention among the other antibiotics indicated for a variety of infectious diseases including lung, abdominal, and skin infections [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A 55% decrease of tigecycline consumption was observed, slightly lower than our study (67.3%). 19 In our study, the patients in cohort 1 had a significantly higher rate of severity of illness explaining the higher mortality observed. The outbreak of A. baumannii infections in cohort 2 led to the concomitant use of colistin and HD of tigecycline, causing a significant deviation in their consumption.…”
Section: -16mentioning
confidence: 42%